Exploring 3-Benzyloxyflavones as new lead cholinesterase inhibitors: synthesis, structure–activity relationship and molecular modelling simulations. Issue 16 (2nd November 2021) - Mughal, Ehsan Ullah; Sadiq, Amina; Ayub, Momna; Naeem, Nafeesa; Javid, Asif; Sumrra, Sajjad Hussain; Zafar, Muhammad Naveed; Khan, Bilal Ahmad; Malik, Fouzia Perveen; Ahmed, Ishtiaq
Abstract: In this protocol, a series of 3-benzyloxyflavone derivatives have been designed, synthesized, characterized and investigated in vitro as cholinesterase inhibitors. The findings showed that all the synthesized target compounds (1–10 ) are potent dual inhibitors of acetylcholinesterase (AChE) and butyrylcholinesterase (BChE) enzymes with varying IC50 values. In comparison, they are more active against AChE than BChE. Remarkably, amongst the series, the compound 2 was identified as the most active inhibitor of both AChE (IC50 = 0.05 ± 0.01 μM) and BChE (IC50 = 0.09 ± 0.02 μM) relative to the standard Donepezil (IC50 = 0.09 ± 0.01 for AChE and 0.13 ± 0.04 μM for BChE). Moreover, the derivatives 5 (IC50 = 0.07 ± 0.02 μM) and 10 (0.08 ± 0.02 μM) exhibited the highest selective inhibition against AChE as compared to the standard. Preliminary structure-activity relationship was established and thus found that cholinesterase inhibitory activities of these compounds are highly dependent on the nature and position of various substituents on Ring-B of the 3-Benzyloxyflavone scaffolds. In order to find out the nature of binding interactions of the compounds and active sites of the enzymes, molecular docking studies were carried out. HIGHLIGHTS: 3-benzyloxyflavone analogues were designed, synthesized and characterized. The target molecules (1–10 ) were evaluated for their inhibitory potential against AChE and BChE inhibitory activities. Limited structure-activity relationship was developed based on the different substituent patterns on aryl part. Molecular docking studies were conducted to correlate the in vitro results and to identify possible mode of interactions at the active pocket site of the enzyme. Communicated by Ramaswamy H. Sarma